Torrefied biomass fuels as a renewable alternative to coal in co-firing for power generation. (15th October 2020) - Sher, Farooq; Yaqoob, Aqsa; Saeed, Farrukh; Zhang, Shengfu; Jahan, Zaib; Klemeš, Jiří Jaromír
Abstract: This study aims to assess the torrefaction of biomass as alternative renewable energy fuel to coal during co-firing. It was evaluated that torrefaction improves biomass grindability to such an extent that it can be used in coal mills with coal in co-firing without capital intensive modification. Torrefaction of beech wood was performed on a batch scale reactor at three different temperatures (200, 250 and 300 °C) with 30 min of residence time. The chemical structural changes in torrefied biomass were investigated with binding energies and FTIR (Fourier transform infrared) analysis. Monocombustion and co-combustion tests were performed to examine the combustion behaviour regarding flue gas emissions (CO, NOx and SO2 ) at 0.5, 1.5 and 2.5 m distance from the burner opening along with fly ash analysis. The FTIR and binding energies showed that lignin hardly affected during light torrefaction while hemicellulosic material was significantly depleted. The Hardgrove grindability index (HGI) was calculated with three methods (DIN51742, IFK and ISO). The medium temperature torrefied biomass (MTTB) yields HGI value in the range of 32–37 that was comparable with HGI of El Cerrejon coal (36–41). A slight change in temperature enabled the torrefied beech wood to be co-milled with coal without capital intensive modification and improved grindability. Comparing the combustion behaviour of single fuels, low temperature torrefied biomass (LTTB) produces less amount of NOx (426 mg/m 3 ), CO (0.002 mg/m 3 ) and SO2 (2 mg/m 3 ) as compared MTTB and raw beech wood. In the case of co-combustion, it was found that blending of coal with raw biomass does not show a stable behaviour. However, premixing of 50% of coal with 50% of torrefied biomasses (MTTB and LTTB) gives most stable behaviour and reduces NOx almost 30% and SOx up to almost 50% compared to coal. The fly ash contents analysis proved that K2 O contents much decreased during co-firing of coal and torrefied fuels that could cause ash related issues during combustion of raw biomass. Graphical abstract: Image 1 Highlights: Torrefaction of beech wood at low and medium temperatures were performed. Chemical structural changes were conducted by binding energies and FTIR analysis. Torrefaction improved particle size distribution and grindability characteristics. The co-combustion of coal and torrefied biomass reduced NOx and SO2 emissions. The fly ash K2 O contents were decreased during cofiring of coal and torrefied biomass.